2011
DOI: 10.1007/s00441-011-1245-z
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin potentiates the interaction of the metalloendopeptidase nardilysin with the neuronal scaffold protein p42IP4/centaurin-α1 (ADAP1)

Abstract: We found colocalization of the neuronal protein p42(IP4) (centaurin-α1; ArfGAP with dual pleckstrin homology domain [ADAP1]), the metalloendopeptidase nardilysin (NRD; involved in axonal maturation and myelination) and tubulin in the cytosol and at the plasma membrane of SH-SY5Y neuroblastoma cells. To examine the importance of tubulin for the interaction of NRD with p42(IP4), we treated cells with nocodazole, which interferes with tubulin polymerization. Nocodazole did not affect the colocalization of p42(IP4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…We found that ADAP1 had a weak but detectable affinity toward microtubules (Fig. 2 A, i), consistent with an earlier report (5). The presence of AMP-PNP-bound, unlabeled KIF13B strongly increased the fluorescence signal of mWasabi-ADAP1 (Fig.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…We found that ADAP1 had a weak but detectable affinity toward microtubules (Fig. 2 A, i), consistent with an earlier report (5). The presence of AMP-PNP-bound, unlabeled KIF13B strongly increased the fluorescence signal of mWasabi-ADAP1 (Fig.…”
Section: Resultssupporting
confidence: 91%
“…For example, in the developing neuron, the protein ADAP1 (ADP-ribosylation factor GTPase-activating protein [ArfGAP] with dual pleckstrin homology [PH] domains 1) has been suggested to control dendrite branching by regulating the small GTPase ARF6. Together with the motor protein KIF13B, ADAP1 is also thought to mediate delivery of the second messenger phosphatidylinositol (3,4,5)-trisphosphate (PIP 3 ) to the axon tip, thus contributing to PIP 3 polarity. However, what defines the function of ADAP1 and how its different roles are coordinated are still not clear.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the brain, ADAP1 was found in neurons of the cortex, hypothalamus, and hippocampus (Sedehizade et al 2002;Moore et al 2007). SH-SY5Y neuronal cell line has been used to study the effects of ADAP1 expression and localization in vitro (Borrmann et al 2011a;Borrmann et al 2011b;Szatmari et al 2013).…”
Section: Major Sites Of Expression and Subcellular Localizationmentioning
confidence: 99%